Dose-response relationship in patients with liver metastases from neuroendocrine neoplasms undergoing radioembolization with 90Y glass microspheres: brief communication - Watanabe, Masao; Leyser, Stephan; Theysohn, Jens; Schaarschmidt, Benedikt; Ludwig, Johannes Maximilian; Fendler, Wolfgang P.; Moraitis, Alexandros; Lahner, Harald; Mathew, Annie; Herrmann, Ken; Weber, Manuel (Journal of nuclear medicine, 2024)
The benefit of multicompartment dosimetry in the radioembolization of neuroendocrine neoplasms is not firmly established. We retrospectively assessed its potential with patient outcome. Methods: Forty-three patients were eligible. The association of mean absorbed dose (MAD) for tumors and treatment response was tested per lesion with a receiver operating characteristic curve analysis, and the association of MAD with progression-free survival (PFS) and overall survival was tested per patient using uni- and multivariate Cox regression analyses. Results: The area under the curve for treatment response based on MAD was 0.79 (cutoff, 196.6 Gy; P < 0.0001). For global PFS, grade (grade 2 vs. 1: hazard ratio [HR], 2.51; P = 0.042; grade 3 vs. 1: HR, 62.44; P < 0.001), tumor origin (HR, 6.58; P < 0.001), and MAD (HR, 0.998; P = 0.003) were significant. For overall survival, no prognostic parameters were significant. Conclusion: In line with prior publications, a MAD of more than 200 Gy seemed to favor treatment response. MAD was also associated with PFS and may be of interest for radioembolization planning for neuroendocrine neoplasm patients.
Im Titel ist die Zahl 90 bei "90Y Glass Microspheres" hochgestellt
Gesehen am 10.03.2025